2020
DOI: 10.33306/mjssh/93
|View full text |Cite
|
Sign up to set email alerts
|

Reason to Believe: Religiosity, Resilience, and Self-Efficacy Among Malaysian Indian Adolescent

Abstract: The emerging incidence of mental health-related illness such as depression, suicide, and deliberate self-harm has elevated gradually among Malaysian Indian adolescents. This disorder constitutes a significant health risk which leads to further exploration of protective factors. Thus, the purpose of this study is to investigate the relationship between religiosity, resilience, and self-efficacy among Malaysian Indian adolescents. Therefore, a sample of 86 respondents (40 males, 46 females) has been selected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…One finds Malay folks in Madagascar, Comoros, the Hadramawt, Ceylon, and Burma. Likewise, archaeological evidences of sea-faring Indians are found all over Southeast Asia and their religious influence is noticeable (Ganaprakasam et al 2020). The animistic practices of the pre-Islamic Malays; the diffusion of Sanskrit/Tamil language among the Malays; the secluded religion of Bali Hinduism; the spread of Ramayana as a folk art; the splendour of Angkor Wat (12th century AD or earlier) and the Borobodur (9th century AD); and even some royal rites and customs all attest to this very large context.…”
Section: The Place Of Temples In the Malaysian Hindu Communitymentioning
confidence: 99%
“…One finds Malay folks in Madagascar, Comoros, the Hadramawt, Ceylon, and Burma. Likewise, archaeological evidences of sea-faring Indians are found all over Southeast Asia and their religious influence is noticeable (Ganaprakasam et al 2020). The animistic practices of the pre-Islamic Malays; the diffusion of Sanskrit/Tamil language among the Malays; the secluded religion of Bali Hinduism; the spread of Ramayana as a folk art; the splendour of Angkor Wat (12th century AD or earlier) and the Borobodur (9th century AD); and even some royal rites and customs all attest to this very large context.…”
Section: The Place Of Temples In the Malaysian Hindu Communitymentioning
confidence: 99%
“…Sejalan pula dengan hasil penelitian yang dilakukan oleh (Ganaprakasam & Selvaraja, 2020), (Ugwuanyi dkk., 2021) dan (Yeo dkk., 2016) yang mengungkapkan bahwa siswa yang mengalami kecemasan ujian kemudian mendapatkan treatment CBT dilaporkan mengalami penurunan kecemasan ujian setelahnya. Bahkan penemuan studi yang lain yang dilakukan oleh (Lovina & Chilota, 2021) bahwa terapi intervensi CBT mengurangi kecemasan ujian matematika siswa yang terpapar CBT.…”
Section: Hasilunclassified
“…Kecemasan ujian merupakan masalah penting di kalangan siswa dalam berbagai konteks pendidikan, karena hal ini bagian dari faktor universal yang secara negatif mempengaruhi prestasi akademik siswa (Ganaprakasam & Selvaraja, 2020). Kecemasan ujian juga menurut Jing G (2007) (dalam Golchin Binandeh and Javad Sahebi Koozekonan, 2022) adalah salah satu kecemasan situasional yang terkait erat dengan kinerja dan prestasi akademik jutaan pelajar dan mahasiswa di pusat-pusat pendidikan.…”
Section: B Pembahasanunclassified
See 1 more Smart Citation
“…Legally, the move to decriminalize suicide attempts has the potential to encourage more help-seeking behavior. Religiously, Fernandez and colleagues argue that all primary religions in Malaysia disprove self-injury and instead encourage them to seek professional help ( 29 ), while another study has shown religiosity providing a positive effect on resilience and self-efficacy ( 30 ). Further studies may be required to address this issue from the NSSI point of view.…”
Section: Introductionmentioning
confidence: 99%